Management Of Madrasah Diniyah Takmiliyah Curriculum Integration In Formal Institutional Units In Improving The Quality Of Graduates - Lukman Sholeh (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze and understand about the Management of Integration of the Madrasah Diniyah Curriculum with Formal Institutions in Improving the Quality of Graduates at Nurul Jadid Islamic Boarding School, Paiton, Probolinggo. This research uses a qualitative approach type of case study. Data collection techniques are carried out through observation, interviews and documentation. Data analysis starts from presenting data, reducing data and ending with drawing conclusions. The results showed that the management of the integration of non-formal madrasah diniyah curriculum in formal education units was carried out by developing the previous integration model. The author calls it the "Curriculum Integration Development Model". In this model explained, first, planning is carried out combining administrative, arena and inverted models. Second, the implementation is carried out by developing two models, namely fragmented models in scientific disciplines and learning sub-units and shared models between scientific and learning disciplines. Third, the evaluation is carried out by developing a stufflebeam's evaluation model, without including curriculum context assessment.